Processing and Bread Making in Sari Mart's Household Industry in Anggoeya Kelurahan, Poasia District Kendari City - Sailila, Annur Babatia; Herdhiansyah, Dhian; Syukri, Muhammad; Asriani, Asriani (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2023)
This research aims to determine the process of processing and making bread at the Sari Mart Home Industry in Anggoeya Village, Poasia District, Kendari City. Data collection was carried out using interview and documentation methods. The analysis used is descriptive. Based on research results, the production process of the Sari Mart Home Industry bread business starts with the process of providing raw materials of 100 kg of wheat flour for all flavor variants, weighing the ingredients according to the measurements using one worker, the mixer process of 1 unit of machine with a capacity of 15 kg, the molding process according to the size of 1 machine unit using one worker, the topping filling process using one worker, the developing process taking a maximum of 5 hours, the oven process taking a maximum of 30 minutes with a temperature of 1800 cc, and the packaging process using three workers.